Співвідношення комерційного найменування з іншими правовими категоріями - Старчук, О.; Starchuk, O. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті висвітлено сутність комерційного найменування в умовах сьогодення. Проаналізовано питання співвідношення комерційного найменування з іншими правовими категоріями, такими як фірмове найменування, комерційне позначення, найменування юридичної особи. Обґрунтовано окремі пропозиції щодо вдосконалення чинного законодавства про комерційні найменування.As legislation so civil science in order to indicate the name of the civil cycle participant use various legal terms, «company», «company name», «trade name», «commercial designation», «name of the juridical person» and so on. According to the civil law modern doctrine the concept of investigation of commercial designation and its legal mechanism is impossible without coordinate the terminology that use for the designation of the intellectual property object. The article focuses on the nature of commercial name at present time. The scientific and well-grounded analysis of different scientists’ approaches as for the definition correlation of the commercial name of with other legal categories is highlighted. On this basis the author suggests the perfection of civil legal relationships adjusting. The issue of commercial name’s correlation of other legal categories such as commercial sign, title of a legal person is analyzed. Some suggestions for improving the current legislation on commercial signs are highlighted.
Commercial Name’s Correlation With other Legal Categories
Keywords: комерційне найменування; фірмове найменування; комерційне позначення; commercial name; brade name; commercial sign